Penerapan Standar Operasional Prosedur Dalam Pemeriksaan Area Pintu Utama Oleh Aviation Security Di Bandar Udara Internasional Zainuddin Abdul Madjid Lombok - Lalu Bendi Albayani Akbar; Teguh Ariebowo (Student Research Journal, 2023)
At every airport there must be a limited security area (Security Restricted). areas). Security Restricted Areas are certain areas within the airport which are identified as a high risk area for use by aviation purposes, operation of airports, and other interests where the area is carried out supervision and to enter will be carried out a security check. Aviation officer Security must be able to act decisively in accordance with standard operating procedures inspection of anyone who enters the airside, as well as ensuring security and airport safety. The purpose of this study is to determine the application of standards operational procedures in checking the main door area by Aviation Security at the Airport International Airport Zainuddin Abdul Madjid Lombok. The method used in this research is using the research method qualitative where researchers conduct interviews, documentation, and direct observation in data collection. The interview used is semi-interview structured and researchers conducted interviews with the Avsec supervisor, Avsec junior and Avsec basic. The results of the research describe the answers of the informants and the data obtained from the field. The results of this study include the application of operational standards procedures in checking the main door area by Aviation Security at the Airport International Zainuddin Abdul Madjid Lombok. The results of this study are the lack of implementation of standard operating procedures during an inspection of the main door area by Aviation Security at the International Airport Zainuddin Abdul Madjid Lombok. lack of SOP implementation due to lack Avsec personnel in carrying out inspections and the lack of facilities available at the post The main door.